Meta-Analysis: Randomized Trials of Lactobacillus plantarum on Immune Regulation Over the Last Decades - Zhao, Wei; Peng, Chuantao; Sakandar, Hafiz Arbab; Kwok, Lai-Yu; Zhang, Wenyi (Frontiers in Immunology, 2021)
Lactobacillus (L.) plantarum strains, belong to lactic acid bacteria group, are considered indispensable probiotics. Here, we performed meta-analysis to evaluate the regulatory effects of L. plantarum on the immunity during clinical trials. This meta-analysis was conducted by searching across four most common literature databases, namely, Cochrane Central Register of Controlled Trials, Web of Science, Embase, and PubMed. Clinical trial articles that met the inclusion and exclusion criteria were analyzed by Review Manager (version 5.3). p value <0.05 of the total effect was considered statistically significant. Finally, total of 677 references were retrieved, among which 6 references and 18 randomized controlled trials were included in the meta-analysis. The mean differences observed at 95% confidence interval: interleukin (IL)-4, -0.48 pg/mL (-0.79 to -0.17; p<0.05); IL-10, 9.88 pg/mL (6.52 to 13.2; p<0.05); tumor necrosis factor (TNF)-α, -2.34 pg/mL (-3.5 to -1.19; p<0.05); interferon (IFN)-γ, -0.99 pg/mL (-1.56 to -0.41; p<0.05). Therefore, meta-analysis results suggested that L. plantarum could promote host immunity by regulating pro-inflammatory and anti-inflammatory cytokines.